Virtual Reality-Mediated Language Learning: A Case Study of Immersive Learning in the Metaverse - Thrasher, Tricia; Christoforou, Maria; Ijiri, Amelia (My University, 2024)
With the COVID-19 pandemic exacerbating educators' reliance on digital tools, virtual reality (VR) has become more prevalent in education. VR has also become more accessible through mainstream headsets (e.g., Meta Quest 2). VR offers immersive, low-risk environments for students to engage in authentic language interactions. However, the integration of VR into language education remains exploratory, often relying on commercial off-the-shelf VR applications which were not designed for education. Moreover, existing studies on VR are largely short-term and lack pedagogical depth. This case study addresses these gaps by documenting two language students' experiences learning English in Immerse, the first VR platform designed specifically for language teaching and learning, over an eight-week period. By exploring long-term immersion and pedagogical implications, the study contributes to understanding VR's potential in fostering meaningful language learning experiences.
Keywords: Virtual Reality-mediated language learning; Metaverse; Immersive language learning